Determining The New Yotta Snack Photo Factors through Kansei Engineering Approach - Nofias Fajri; Firdhani Faujiyah (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
The Covid-19 pandemic has had a significant impact on social habits in Indonesia. Conditions that require society to reduce interaction directly result in changes in the shopping style and diet of society. As such changes, this phenomenon also resulted in the food business’s transition into a versatile online. This causes the food menu to be selected based on the picture and rating of food, So the picture becomes one of the important things in attracting consumer interest in choosing a certain type of food. Yotta Snack is one of the new products of Yotta that is not so well known to the public. Food photography is one of the ways that consumers can use to increase their desire for food. Kansei engineering is one of the methods that can be used in designing aproduct that fits the consumer's wishes. This research aims to determine the factors of Yotta’s photo products snack with a Kansei engineering approach. Theresearch of 100 responders got 27 words of kansei. The analytics factor came up with 6 groups of Kansei words in pairs. Six words Kansei pairing is a neat mess, Fresh wilted, creative monotonous, not aesthetic, The darkness of light, It's unclear.